Genotoxic and cytotoxic potential of Alternanthera Bettzickiana, an important ethno-medicinal plant - Akhtar, M. F.; Sharif, A.; Saleem, M.; Saleem, A.; Akhtar, B.; Raza, M.; Ijaz, H.; Shabbir, M.; Ali, S.; Sharif, A.; Nasim, M. B.; Peerzada, S. (Cellular and Molecular Biology, 2017)
The present study was carried out to investigate the mutagenic and cytotoxic potential of n-hexane and aqueous-methanolic whole plant extracts of Alternanthera bettzickiana. Aqueous-methanolic and n-hexane extracts of Alternanthera bettzickiana extracts were assessed for the mutagenic potential with Salmonella tester strains TA-100 and TA-102 in the presence and absence of the rodent enzyme activation system and cytotoxic potential was assessed by MTT assay. Aqueous-methanolic extract showed the presence of saponins, tannins, terpenoids, flavonoids and glycosides. However n-hexane extract revealed the presence of tannins and terpenoids only. It was found that a concentration as low as 15mg/mL of both extracts was more mutagenic to the TA 102 tester strain than TA-100. Hexane whole plant extract of Altenanthera bettzickiana was more mutagenic than aqueous-methanolic extract considering revertant colonies of TA 100 strain. Aqueous-methanolic and n-hexane whole plant extracts of Altenanthera bettzickiana showed higher mutagenic potential in the presence of the enzyme activation system. Mutagenicity of aqueous-methanolic extract increased with an enzyme activation system in case of TA 100 whereas mutagenicity of n-hexane extract decreased in the presence of the enzyme activation system with TA 100 and TA 102 strains. Aqueous-methanolic and n-Hexane whole plant extracts of Alternanthera bettzickiana showed an IC-50 of 493 and 456 µg/mL in BHK-21 cells respectively. It can be concluded that Altenanthera bettzickiana exhibited mutagenic activity in a bacterial reverse mutation assay with and without enzyme activation systems. However, it showed limited cytotoxicity to BHK-21 cells.